Physical Activity With Eduball Stimulates Graphomotor Skills in Primary School Students - Wawrzyniak, Sara (2021)
Despite the general agreement that the interdisciplinary model of physical education (PE), based on the incorporation of core academic subjects into the PE curriculum, stimulates the holistic development of students, there is still a lack of methods for its implementation. Therefore, Eduball was created, i.e., a method that uses educational balls with printed letters, numbers, and other signs. Numerous studies have shown that children participating in activities with Eduballs can develop their physical fitness while simultaneously improving their academic performance, particularly in math and language, including some writing skills. However, little is known about the effects of Eduball on children’s graphomotor skills, which are key for the academic performance of students throughout the entire schooling process. Here, we investigate whether 6-month participation in PE with Eduball stimulates graphomotor skills in primary school students, such as drawing prehandwriting letter patterns on unlined or lined paper and rewriting text on unlined or lined paper. Our results show that the Eduball class (N = 28) significantly improved these skills compared to the control class (N = 26) participating in traditional PE. For example, students from the experimental group wrote with a lower pen pressure and better stability of the line, in contrast to those from the control group. Therefore, this study demonstrates that the Eduball method successfully supports teachers in developing graphomotor skills in children. More broadly, our findings make clear once again that there is the need to integrate physical and cognitive development in education, which can be achieved by using an interdisciplinary model of PE.